The Disturbance of Gaze in Progressive Supranuclear Palsy: Implications for Pathogenesis - Chen, Athena L.; Riley, David E.; King, Susan A.; Joshi, Anand C.; Serra, Alessandro; Liao, Ke; Cohen, Mark L.; Otero-Millan, Jorge; Martinez-Conde, Susana; Strupp, Michael; Leigh, R J. (Frontiers in Neurology, 2010)
Progressive supranuclear palsy (PSP) is a disease of later life that is currently regarded as a form of neurodegenerative tauopathy. Disturbance of gaze is a cardinal clinical feature of PSP that often helps clinicians to establish the diagnosis. Since the neurobiology of gaze control is now well understood, it is possible to use eye movements as investigational tools to understand aspects of the pathogenesis of PSP. In this review, we summarize each disorder of gaze control that occurs in PSP, drawing on our studies of fifty patients, and on reports from other laboratories that have measured the disturbances of eye movements. When these gaze disorders are approached by considering each functional class of eye movements and its neurobiological basis, a distinct pattern of eye movement deficits emerges that provides insight into the pathogenesis of PSP. Although some aspects of all forms of eye movements are affected in PSP, the predominant defects concern vertical saccades (slow and hypometric, both up and down), impaired vergence, and inability to modulate the linear vestibulo-ocular reflex appropriately for viewing distance. These vertical and vergence eye movements habitually work in concert to enable visuomotor skills that are important during locomotion with the hands free. Taken with the prominent early feature of falls, these findings suggest that PSP tauopathy impairs a recently-evolved neural system concerned with bipedal locomotion in an erect posture and frequent gaze shifts between the distant environment and proximate hands. This approach provides a conceptual framework that can be used to address the nosological challenge posed by overlapping clinical and neuropathological features of neurodegenerative tauopathies.